2015
DOI: 10.1093/pa/gsv053
|View full text |Cite
|
Sign up to set email alerts
|

Leaving the House: The Experience of Former Members of Parliament Who Left the House of Commons in 2010

Abstract: This article reports the findings of a large-scale survey investigating the experiences of the large number of MPs who left parliament following the 2010 general election. We have found that: the widely-held perception that MPs make a smooth transition into lucrative private sector employment after leaving Parliament is largely mistaken; the MPs' expenses scandal has seriously undermined the status of MPs and, as such, may also have made a career in Parliament less enticing for good prospective parliamentary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 11 publications
(7 reference statements)
1
41
0
1
Order By: Relevance
“…This contrast may have led to greater punishment of female MPs compared to their male counterparts. 41 A recent large-scale survey after the expenses scandal concluded that female British MPs in particular felt that their family lives were strained (Byrne and Theakston 2015). Our findings can also be related to the work of Gagliarducci and Paserman (2012), who find that the probability of early termination of Italian city councils is higher when the mayor is a female and that this gender effect increases in male-dominated legislatures, highlighting the hurdles faced by female politicians in a male-dominated environment.…”
Section: Discussionmentioning
confidence: 62%
“…This contrast may have led to greater punishment of female MPs compared to their male counterparts. 41 A recent large-scale survey after the expenses scandal concluded that female British MPs in particular felt that their family lives were strained (Byrne and Theakston 2015). Our findings can also be related to the work of Gagliarducci and Paserman (2012), who find that the probability of early termination of Italian city councils is higher when the mayor is a female and that this gender effect increases in male-dominated legislatures, highlighting the hurdles faced by female politicians in a male-dominated environment.…”
Section: Discussionmentioning
confidence: 62%
“…Those who struggled to find employment, paid or voluntary and/ or where little use made of the skills and experience gained in office had a more difficult adjustment, resonating with Theakston et al, (2007). Contrary to public perception, there is no revolving door in the UK between political office and the corporate boardroom for most (Byrne and Theakston, 2016). Skills could be far better used, both to bolster the evolving new identity of former politicians and to benefit employers, political parties and wider civic society.…”
Section: Predicting the Impact Of The Loss Of Officementioning
confidence: 98%
“…In the UK, Theakston has led work on Westminster MPs leaving office using mostly survey data (Theakston, Gouge & Honeyman, 2007;Byrne & Theakston, 2016) with an unspecified number of interviews. This work, and Kwiatowski's (2015) interviews with MPs, demonstrates the difficulties experienced by many in adjusting to life outside the House of Commons.…”
Section: Scholarly Work Specifically On Former Politicians Emerged Inmentioning
confidence: 99%
“…On average, being a year older increases the expected rate of EU-related messages by 1.1 per cent. Given that age is the single most important reason for not seeking re-election (Byrne & Theakston, 2015), one could argue that older MPs are less concerned with losing their seats and therefore that they can allow themselves to communicate low salient affairs as well. With respect to gender, female MPs are expected to post a 27.1 per cent smaller share of tweets on EU affairs.…”
Section: Determinants Of Communicating Eu Affairsmentioning
confidence: 99%